Kecemasan dalam mencintai: Telaah psikologis anxious attachment - hasanah, nur hidayatul (Maliki Interdisciplinary Journal, 2026)
Anxious attachment is an emotional attachment pattern characterized by excessive anxiety in interpersonal relationships, particularly in romantic relationships. Individuals with this attachment style tend to have a strong need for emotional closeness, attention, and validation from their partners. Uncertainty within relationships often triggers intense emotional responses, such as fear of abandonment, overthinking, and difficulties in regulating emotions independently. This article aims to examine anxious attachment from a psychological perspective by highlighting its key characteristics, its impact on emotional regulation, and its implications for interpersonal relationship dynamics. The discussion indicates that anxious attachment significantly affects individual psychological well-being and the quality of relationships. Therefore, understanding this attachment pattern is essential as a foundation for developing more adaptive emotion regulation, healthy communication, and balanced interpersonal relationships.